Structural characteristics of polysaccharide from Zingiber striolatum and its effects on gut microbiota composition in obese mice - Jiang, Wei; Hu, Ying; Zhu, Zhenyuan (Frontiers in Nutrition, 2022)
To investigate a polysaccharide from Zingiber striolatum favorably modulates gut microbiota in mice fed a high-fat diet. Zingiber striolatum was utilized to extract the crude polysaccharide CZSP, which was subsequently refined using DEAE-52 cellulose and Sephadex G-150 to yield the novel polysaccharide ZSPP-1. ZSPP-1 was an acidic heteroglycan made up of galactose, mannose, glucose，xylose, arabinose, glucuronic acid and galacturonic acid with an average molecular weight of 1.57×106 Da. The structure of ZSPP-1 was investigated by FT-IR, methylation and NMR analysis, and the results denoted that the linkage structure types include T-Manp-linked, β-Xylp-(1,2)-linked, β-Galp-(1,4)-linked, α-GlcpA-(1,6)-linked, β-Arap-(1,4)-linked, α-Glcp-(1,3,4,6)-linked, α-Glcp-(1,2)-linked and β-T-Xylp-linked, in which β-Galp-(1,4)-linked and α-GalpA-(1,4)-linked might be the main linkage. The results of the intervention experiments showed that ZSPP-1 changed the intestinal flora structure of the Firmicutes and Bacteroidetes in obese mice, and promoted the growth of beneficial bacteria such as Akkermansia, Lactobacillus and Bacteroides in the intestine. It also restored the imbalanced flora structure due to high-fat diet to normal. It also restored the imbalanced flora structure due to high-fat diet to normal. Zingiber striolatum polysaccharides presented a considerable advantage in alleviating high-fat diet induced obesity, which indicates that it can be further exploited as a natural functional food resource.